2018
DOI: 10.1104/pp.18.00921
|View full text |Cite
|
Sign up to set email alerts
|

Recursive Paleohexaploidization Shaped the Durian Genome

Abstract: The durian (Durio zibethinus) genome has recently become available, and analysis of this genome reveals two paleopolyploidization events previously inferred as shared with cotton (Gossypium spp.). Here, we reanalyzed the durian genome in comparison with other well-characterized genomes. We found that durian and cotton were actually affected by different polyploidization events: hexaploidization in durian ;19-21 million years ago (mya) and decaploidization in cotton ;13-14 mya. Previous interpretations of share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…Ks were estimated using the Nei–Gojobori approach implemented by BioPerl Statistical module (Nei and Gojobori, ). We adopted a kernel function analysis of Ks distribution of colinear homologs within or between different genomes according to our previous reports (Wang et al, ; Wang et al, ). Ks distribution was viewed as a mix of multiple normal distributions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ks were estimated using the Nei–Gojobori approach implemented by BioPerl Statistical module (Nei and Gojobori, ). We adopted a kernel function analysis of Ks distribution of colinear homologs within or between different genomes according to our previous reports (Wang et al, ; Wang et al, ). Ks distribution was viewed as a mix of multiple normal distributions.…”
Section: Methodsmentioning
confidence: 99%
“…We estimated the evolutionary rates of ECH‐produced duplicated genes, corrected according to our report (Wang et al, ). The maximum likelihood estimate µ from inferred Ks means of ECH‐produced duplicated genes was aligned to have the same value of those of grape.…”
Section: Methodsmentioning
confidence: 99%
“…These duplicated genes provide enormous opportunities for biological innovation [37][38][39]. It has been more and more evident that whole-genome duplications have contributed to the origination, fast divergence [40], establishment of major plant taxa [41,42], such as seed and flowering plants [43], and furthermore the subsets of the latter monocots and dicots [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…(Jaillon et al, 2007;Jiao et al, 2011;Wang et al, 2017). Cotton was affected by a decaploidization event, likely shared with the other Gossypium relatives, but not the non-Gossypium Malvaceae plants, such as durian and cacao (Wang et al, 2016(Wang et al, , 2019. This means that, if no gene loss had occurred, a grape gene would have one cacao ortholog and five orthologs in collinear positions in Gossypium raimondii (DD).…”
Section: Introductionmentioning
confidence: 99%
“…Using grape orthologs as a reference, the comparison of cacao and cotton genes showed that cotton genes evolved 19 and 15% faster at synonymous and non-synonymous substitution sites than their cacao homologs, respectively. Cacao was used to assess the difference in evolutionary rates between durian and cotton, indicating that after division from cacao, cotton evolves about 64% faster than durian (Wang et al, 2019). The difference between cotton paralogs is greater than the difference between them and cacao orthologs due to the increased rate of cotton evolution.…”
Section: Introductionmentioning
confidence: 99%